Clinical analysis on hemifacial spasm treated by microvascular decompression - Zhong-hua XU; Yan-shen TANG; Yao-hua YAN (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
Objective To analyze the operating points and evaluate the therapeutic efficacy and safety of microvascular decompression (MVD) for hemifacial spasm (HFS). Methods The clinical data of 54 patients with HFS underwent MVD were analyzed retrospectively. The offending vessels included anterior inferior cerebellar artery (AICA) in 32 cases (59.26%), posterior inferior cerebellar artery (PICA) in 11 cases (20.37%), vertebral artery (VA) in 5 cases (9.26%), both AICA and PICA in 6 cases (11.11%). Results After an average of 2 years of follow-up, 46 cases (85.19%) were completely relieved, 5 cases (9.26% ) were markedly relieved, 2 cases (3.70% ) were partially relieved, and one case (1.85% ) had no significant change. The total effective rate was 94.44% (51/54). There were 4 cases (7.41% ) with mild facial paralysis, 2 cases (3.70% ) with hearing loss, and 4 cases (7.41% ) with delayed resolution after operation, and no intracranial hematoma, intracranial infection, cerebrospinal fluid (CSF) leakage or death occurred during the perioperative period. Conclusions MVD is effective and safe in the treatment of HFS. Adept operation skills, correct identification of offending vessels, and effective decompression are the key to successful operation. Intraoperative electrophysiological monitoring can be used to identify the effect of operation and reduce postoperative complications.